Pastoral Counselling as a Framework for Enhancing Women’s Quality of Life in Nigeria - Sabina Nwakaego Obi; Oyebola Olubunmi Igeleko (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Women play indispensable roles in family life, community development, and nation-building, yet their quality of life in Nigeria remains undermined by persistent challenges. Poverty, cultural restrictions, reproductive health burdens, limited access to education, and gender-based violence continue to affect women's well-being across physical, psychological, social, and spiritual dimensions. Because of the centrality of women to sustainable development, improving their quality of life requires holistic and contextually grounded interventions. The purpose of this conceptual paper is to explore pastoral counselling as a framework for enhancing women's quality of life in Nigeria. Unlike empirical studies, the paper adopts a conceptual research design, synthesising literature from psychology, theology, and counselling, alongside studies on women's wellness in Nigeria. The analysis involved clarifying the quality of life and pastoral counselling constructs, reviewing empirical findings on the barriers to women's wellness, and integrating insights to propose a holistic framework. Findings from the conceptual review highlight that socio-economic hardship, gender inequality, cultural norms, reproductive health issues, and psychological stressors shape women's quality of life. Pastoral counselling addresses these challenges through four domains of intervention: psychoeducation and empowerment, vocational and economic support, spiritual resilience, and psychotherapeutic care. By integrating psychological methods with spiritual resources, pastoral counselling emerges as a culturally sensitive and multidimensional approach to women's wellness. The result is that pastoral counselling should be recognised as more than a religious activity; it is a viable framework for policy, practice, and collaboration among counsellors, NGOs, faith communities, and government. Its conceptual contribution lies in reframing counselling as a holistic pathway for improving women's quality of life and advancing sustainable development in Nigeria.